Empirical Essays in Economics of Education and Labor - Marie Kruse Skibsted (Copenhagen Business School (CBS), 2016)
This thesis focuses on individuals' educational achievements and labor market outcomes in a Danish context. Particularly, the thesis aims at determining the returns to specific tertiary educational decisions and understanding the mechanisms underlying such decisions. These related objectives are addressed using econometric methods applied on Danish micro data. All four chapters are empirical studies and combine data from different sources. The main source of data is an administrative data set obtained from Copenhagen Business School (CBS) that contains detailed educational information on students enrolled at CBS. I combine this data with register data obtained from Statistics Denmark. The educational data is the core of Chapter 2, Chapter 3, and Chapter 4 and defines the sample in these chapters. Chapter 1 relies exclusively on data from Statistics Denmark. Chapter 1 (a joint work with Anders Sørensen from Copenhagen Business School) estimates the wage premium of those with a master's degree in business economics and management when compared to the wages of those with master's degrees in other fields in the social sciences. By means of an Instrumental Variable (IV) approach, we identify the returns to a business education by addressing the endogenous selection of master's programs. Using season of birth as an exogenous determinant of master's degree choice, we find that a master's degree in business economics and management results in a wage premium of around 12% compared to other master's degrees in the social sciences. Moreover, we find that the probability of private sector employment is significantly larger for individuals with a master's degree in business economics and management. Finally, in contrast to the literature that finds significant reductions in the gender wage gap when controlling for educational fields, controlling for a master's degree in business economics and management does not affect the large and robust gender wage gap prevalent in our sample.
hdl:10398/9318
Keywords: 650